2010
DOI: 10.1111/j.1742-4658.2010.07631.x
|View full text |Cite
|
Sign up to set email alerts
|

Large conformational changes in the Escherichia coli tryptophan synthase β2 subunit upon pyridoxal 5′‐phosphate binding

Abstract: To understand the basis for the lower activity of the tryptophan synthase beta(2) subunit in comparison to the alpha(2)beta(2) complex, we determined the crystal structures of apo-beta(2) and holo-beta(2) from Escherichia coli at 3.0 and 2.9 A resolutions, respectively. To our knowledge, this is the first report of both beta(2) subunit structures with and without pyridoxal-5'-phosphate. The apo-type molecule retained a dimeric form in solution, as in the case of the holo-beta(2) subunit. The subunit structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 59 publications
(72 reference statements)
0
5
0
Order By: Relevance
“…The lower maximal ALAS activity observed for the Mtm1p-deficient mitochondria may indicate that the ALAS apoenzyme is unstable in the absence of PLP. Cofactor binding is known to significantly increase the stability of PLP-dependent enzymes, with as much as 30 kcal/mol stabilization of the PLP complex reported for cytosolic aspartate aminotransferase [45], and PLP binding has been reported to induce large conformational changes in the β-subunit of tryptophan synthase [46]. There is also evidence, at least in mammalian cells, for a mitochondrial protease that selectively degrades the ALAS apoprotein [47].…”
Section: Resultsmentioning
confidence: 99%
“…The lower maximal ALAS activity observed for the Mtm1p-deficient mitochondria may indicate that the ALAS apoenzyme is unstable in the absence of PLP. Cofactor binding is known to significantly increase the stability of PLP-dependent enzymes, with as much as 30 kcal/mol stabilization of the PLP complex reported for cytosolic aspartate aminotransferase [45], and PLP binding has been reported to induce large conformational changes in the β-subunit of tryptophan synthase [46]. There is also evidence, at least in mammalian cells, for a mitochondrial protease that selectively degrades the ALAS apoprotein [47].…”
Section: Resultsmentioning
confidence: 99%
“…2B) [23], serine racemase from Rattus norvegicus and Homo sapiens [30], and OASS from S. typhimurium [31]. In tryptophan synthase β from E. coli [32] and l ‐serine dehydratase from Rattus norvegicus (rat liver LSD) [9], a similar domain movement is observed between apo and holo forms of the enzymes. Considering that SeMetDSD crystal was grown in the presence of the inhibitor (isoserine), it is reasonable to assume that SeMetDSD represents the ligand bound closed form of the enzyme while the WtDSD represents the unliganded open form of the enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…Mutation analysis Chimera 1.13 was used to analyse the substrate channel space of tryptophan synthase (PDB: 2dh6), and it was found that the amino acid residues of tryptophan synthase at positions 231 and 382 were located in the loop formed by the substrate channel [24]. The amino acid residue at site 231 was mutated from valine to alanine, and the residue at site 382 was mutated from lysine to glycine, which may change the folding direction of the loop, thus changing the size and shape of channel entrance and promoting mutated enzymatic activity (Fig.…”
Section: Effects Of Temperature Ph and L-serine On The Enzymesmentioning
confidence: 99%